2014
DOI: 10.1561/0700000048
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Enforcement and Compliance: Lessons from Pollution, Safety, and Tax Settings

Abstract: Environmental monitoring and enforcement are controversial and incompletely understood. This survey reviews what we do and do not know about the overall effectiveness, as well as the cost effectiveness, of pollution monitoring and enforcement. We ask five key questions: What do environmental monitoring and enforcement actions look like in the real world? How do we assess environmental compliance and deterrence? Do environmental monitoring and enforcement actions get results? How, why, and when do inspections a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
2

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 110 publications
1
14
0
2
Order By: Relevance
“…In fact, OECD (2011) identified regulations as part of the key instruments for curtailing environmental challenges. Alm and Shimshack (2014) also concluded that environmental monitoring and enforcement actions generate important deterrence effects. Such could include deterring environmental offenders from noncompliance with their obligations, such as ensuring maximum compliance with environmental taxes.…”
Section: Ijesm 146mentioning
confidence: 99%
“…In fact, OECD (2011) identified regulations as part of the key instruments for curtailing environmental challenges. Alm and Shimshack (2014) also concluded that environmental monitoring and enforcement actions generate important deterrence effects. Such could include deterring environmental offenders from noncompliance with their obligations, such as ensuring maximum compliance with environmental taxes.…”
Section: Ijesm 146mentioning
confidence: 99%
“…Should the recommendations of this study implemented in Uganda, Police officer will effectively participate in ESA. Alm and Shimshack (2014) investigated Environmental enforcement and compliance lessons Environmental Management and Sustainable Development ISSN 2164-7682 2019 from pollution, safety and tax settings in U.S.A. The investigation revealed that" although traditional environmental monitoring and enforcement actions generate important deterrence effects, there are limits to such deterrence, meaning that deterrence itself cannot fully explain all patterns of environmental behavior".…”
Section: Environmental Management and Sustainable Developmentmentioning
confidence: 99%
“…The converse is also true: in the absence of third-party tax information return reporting, tax compliance plummets. 13 11 See Alm and McClellan (2012), Alm and Shimshack (2014), and Alm, Martinez-Vazquez, and McClellan (2016). 12 See the many studies listed on the IRS "tax gap" web site at https://www.irs.gov/uac/the-tax-gap.…”
Section: "To Increase Tax Compliance Increase Enforcement"mentioning
confidence: 99%